Model updating of plate composite structure using particle swarm optimization algorithm - Quang, Minh Tran; Bento, Ana Margarida; Tiago, Ferradosa; Sousa, Hélder S.; Duc, Binh Nguyen; Cam, Nhung Nguyen Thi; Campos e Matos, José (ce/papers, 2023)
The Finite Element Method (FEM) is a widely applied method for design calculations in many industries, including civil engineering, textile technology and aerospace. Computational simulation is subject to many uncertain parameters that greatly affect the results of structural analysis and evaluation. This is especially true for structures made of composite materials and complex structures. Determining the exact computational parameters is difficult because the structure involves many materials and components. Not to mention that for some structures, removing some additional components also affects the calculation results. Therefore, the present research aims to propose a simple and straightforward calculation method that ensures the accuracy of the finite element model based on swarm intelligence, namely the Particle Swarm Optimization (PSO) algorithm. The results reveal a good compromise between the laboratory results and the computational simulations for the model scale studied. In this way, an accurate and reliable model can be produced that can be applied to structural health monitoring, design optimization, or reliability analysis.